Changes in transforming growth factor-beta 1 in gingival crevicular fluid following periodontal surgery - (:unkn) unknown (WILEY, 2004)
Objectives: Growth factors play a major part in wound healing, including in the periodontium. However, the presence of growth factors in gingival crevicular fluid (GCF) in humans during periodontal wound healing has not yet been determined. Our hypothesis is that such factors are present in GCF and that changes in their levels might be of value as a prognostic marker of wound-healing activity and therapeutic progress following periodontal surgery. The aim of this study was therefore to measure transforming growth factor-beta1 (TGF-beta1) in GCF collected from sites that have undergone guided tissue regeneration (GTR) and conventional flap (CF) surgery and to compare these with GCF collected from unaffected healthy sites. Materials and Methods: GCF samples were collected, using filter paper strips, at baseline (pre-surgical) and then at intervals up to 26 weeks from 16 patients undergoing GTR and from 11 patients undergoing CF surgery. After elution and acid treatment, TGF-beta1 levels were measured by ELISA. Results: Treatment of periodontal defect sites significantly reduced the mean probing pocket depth (PPD) and improved the mean lifetime cumulative attachment loss (LCAL). Average GCF volumes also significantly increased at all sites at 2 weeks post-surgery and thereafter declined to baseline levels, except at the GTR test sites that were still elevated at 7 weeks. TGF-beta1 could be detected in almost all GCF samples, and 2 weeks after surgery, the average levels increased two-fold at the surgically treated but not at the control sites, which remained unchanged. Conclusion: TGF-beta1 is readily detectable in GCF and increases transiently following periodontal surgery. This suggests that changes in the levels of this growth factor in GCF might be useful for monitoring the progress of periodontal repair and regeneration.
Keywords: flap surgery; gingival crevicular fluid; guided tissue regeneration; transforming growth factor-beta 1; GUIDED TISSUE REGENERATION; POLYPEPTIDE GROWTH-FACTORS; HUMAN INTRABONY DEFECTS; CONTROLLED CLINICAL-TRIAL; HUMAN INFRABONY DEFECTS; LIGAMENT CELLS; BIORESORBABLE MEMBRANES; BONE TURNOVER; FACTOR-BETA; IN-VITRO